Simultaneous occurrence of multiple types of cutaneous tuberculosis (TVC and PNT) with internal organ tuberculosis (PTB). (Mymensingh Medical Journal, 2007)
The abstract of this article is available on the PubMed website.Mymensingh Med J. 2007 Jan;16(1):108-12